FEE SYSTEM ANALYSIS AND ITS DISPARITY UNDER BSI SMART AGENT SERVICES : In The Samsarah Perspective - Khalidin, Bismi; Zahara, Alfi (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
The agreement of the two parties in entering into an agreement is part of the legal requirements for the validity of the agreement. The purpose of this study is to determine the fee rate determined by BSI management, the fee disparity set by BSI Smart Agent management with similar services, and the perspective of the samsarah contract on fee levels and their disparities with similar services. This research explores a descriptive method and the data was collected through interviews and documentation. The study found that, based on data analysis in the agreement, BSI management has arranged systematically and clearly regarding the level of fees in which the agent will receive. In the agreement, it is stated that the agent must comply with all the conditions set. The fee disparity occurs because BSI management has set rules for fee rates but the agent does not understand the rules that have been approved and ratified by both parties, in which this action causes the contract requirements not to be fulfilled. This study concludes that in reality there is a problem in the implementation of the samsarah contract carried out by the agent, namely applying a different fee system from the contents of the agreement without the consent of both parties